“Pengaruh Supervisi Manajerial dan Supervisi Akademik terhadap Kinerja Guru ” (Studi Kuantitatif di Lingkungan Yayasan Amal Bakti Amal Soleh Kota Bogor) - Yurnita, Fitri (Journal of Education, 2025)
This study analyzes the impact of managerial and academic supervision on the performance of teachers in the Amal Bakti Amal Soleh Foundation in Bogor City. Teacher performance significantly impacts the education system's quality, and supervision is one of the most important strategies to improve it. This research conducted quantitative approach with a causal associative research design. The population in this study were all 48 teachers of MTs and MA in the foundation, and the sampling technique used was population study (census). Data collection was conducted using a questionnaire based on a Likert scale, and the data was analyzed using Structural Equation Modeling (SEM) method with SmartPLS 4.0 software. The findings revealed that: (1) Managerial supervision positively and significantly impacts teacher performance; (2) Academic supervision positively and significantly impacts teacher performance. Both supervisory variables simultaneously provide strong influence toward teacher performance improvement. This research implies the need for principals to actively exercise their dual roles as managers and academic supervisors to devise systematic and continuous supervisory plans to optimize teacher performance towards excellent educational quality.